Degradation Behaviors of Adhesion Strength of Structural Adhesive for Weld-Bonding under High Temperature and Humidity Conditions. (2017) - Tomita, Yugo; Shohji, Ikuo; Koyama, Shinji; Shimizu, Seigo
Abstract: To investigate degradation behaviors of a structural adhesive for weld-bonding under high temperature/humidity conditions, a lap shear test was conducted and fracture surfaces were observed. In aging at 40 o C in 95% R. H., the lap shear strength scarcely changed until 500 h although hydrolysis of the adhesive gradually progressed with aging. The fracture mode was cohesive fracture. In aging at 80 o C in 95% R. H., the lap shear strength decreased and the main fracture mode changed from cohesive fracture to interfacial fracture with aging. Hydrolysis of the adhesive progressed with aging until 500 h and the degree of hydrolysis ( D h ) saturated in the aging time over 500 h. A linear negative correlation was seen between the lap shear strength and the area ratio of interfacial fracture. From the analysis results of relationship between the lap shear strength and D h, it was found that the degradation of the adhesive strength was mainly caused by the deterioration of the adhesive by hydrolysis in the early stage of aging and further deterioration proceeded by the occurrence of interfacial fracture in the long-term aging.